ANALISIS PENGENDALIAN KUALITAS PRODUK PADA PT XYZ - Toni Parindo Rumapea; Arsyad Sumantika (Computer Science and Industrial Engineering, 2025)
Quality control is important to maintain the company's position in the eyes of consumers. PT XYZI is a company that produces electronic devices, one of the products has a defect rate that exceeds the company's target, the company's target for defective products is 2% and it is known that the highest defect percentage is 6.28% during the period April 2024 to March 2025. This study aims to as to provide improvement solutions.The research method used is Failure Mode and Effect Analysis (FMEA) to determine the severity rating, Occurance, detection and RPN calculation. The next stage uses Root Cause Analysis (RCA) to identify the root cause of the defect from the highest RPN value. Based on the results of the study, the failure mode from the calculation of the highest RPN value of 378 is the tombstone defect, the RPN value of 315 is the no wetting defect. The improvement solution for tombstone defects is special training for technicians to make machine adjustments. The improvement solution for the no wetting defect is an increase in operator accuracy in checking the pcb after printing.